The effects of exercise - Kernohan, Helen (My University, 1904)
Introduction: We find that exercise not only causes the muscles to become larger but makes them healthier and being thus they can to a better advantage preform their work. Also all the vital organs are kept in working order and the body being, in such a sound condition cannot help but contain a well developed mind. Thus exercise is found to be one of the essentials to long livety and endurance.
Citation: Kernohan, Helen. The effects of exercise. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Exercise; Health; Healthy Habits; Results of Exercise; Theses